Post Traumatic Orbital Decompression: Our Experience (Indian Journal of Public Health Research & Development, 2021)
This study is an analysis of five cases of orbital trauma causing proptosis, paralysis of extraocular muscleswith or without associated visual failure. All the cases were treated by a ENT and Neurosurgical team. Eithera frontal craniotomy or a lateral orbitotomy was performed. Plain X-rays of the skull and ComputerisedTomography (C.T. Scanning) were the main investigations. Results were encouraging both functionally andcosmetically. Early diagnosis and an aggressive approach to orbital decompression can achieve good results.
Keywords: Head Injury, Proptosis, Head injury complications, Post traumatic blindness.